Persepsi Diri Seorang Gay dalam Hubungan Romantis dengan Pasangannya - Nathania Sekar Andwini; Aloysius Soesilo (Universitas Kristen Maranatha, 2018)
Self-perception theory states that people can understand their attitudes and interests because they make inferences about their behavior. This research has attempted to focus on self-perception as it relates to the process of becoming a gay and the role it plays in a gay’s romantic relationships. This less frequently investigated topic is expected to provide a better understanding about psychological experiences a gay has gone through. This qualitative study is a case study of one participant chosen in accordance with the criteria set up for the research. Collection of data was primarily done through observations and interviews.. The findings have shown that the life journey of the participant’s becoming a gay reflected a complex process and was influenced by many factors, internal and external. The negative self-perception of the participant has adversely affected his relation with other people and God. Along the journey, the participants had gone through internal conflicts that so far has not been successfully been coped with.Contrary to what people generally believe, becoming a gay for the participant has been a long and torturous process. Further research needs to be done by adding the number of participants with the same and different sexual orientations to obtain a more comprehensive understanding about the self-perception and its role in these groups of populations.